Duration of multipacting processes and discharges in the linac of ions - Lobzov, L.D.; Shulika, N.G.; Shulika, O.N.; Belan, V.N. (Вопросы атомной науки и техники, 2009)
It is experimentally shown that multipactor processes may be as harmful as other of parasitic discharges and cause significant disturbance in resonator electrodynamic characteristics of an accelerating structure. The disturbance may be evaluated by pulse-shape distortions of a reference rf voltage impulse. Control over duration of multipactor processes within diode gaps of a linac is effected by varying parameters of a self-sustained oscillation system formed by two independent positive feedback circuits (PFC). If two synchronous rf voltage pulses of given amplitude superpose in the accelerating structure, there occurs an impediment to multipactor processes. As this takes place, multipactor processes display minimal duration and do not affect acceleration stability.